Solubility Prediction of Paracetamol in N-Methyl-2-pyrrolidone + Ethanol + Water Mixtures at 25 °C - Ahmadi, Farahnaz; Sadrjavadi, Komail; Mohammadi, Ghobad; Separham, Amir; Barzegar-Jalali, Mohammad; Khoubnasabjafari, Maryam; Jouyban, Abolghasem (Journal of Applied Solution Chemistry and Modeling, 2014)
The solubility of paracetamol in N-Methyl-2-pyrrolidone (NMP) + ethanol and NMP + ethanol + water solvent mixtures at 25°C was determined using the shake flask method. The generated data extended the solubility database of pharmaceuticals and also was used to assess the solubility prediction capability of the Jouyban-Acree model in NMP + ethanol + water mixtures. The accuracy of the predicted solubilities was evaluated by the mean percentage deviation (MPD) between the predicted and experimental solubilities. The MPD of the Jouyban-Acree model for predicting the solubility of paracetamol in NMP + ethanol + water mixtures at 25°C was 14.6 %.